A sensitive chemiluminescence method for quantification of the oxidative burst in grapevine cells and rice roots. (June 2021) - Heyman, Lisa; Ferrarini, Enrico; Sanchez, Lisa; Barka, Essaid Ait; Höfte, Monica
Highlights: High-throughput L-012-based method for oxidative burst quantification in roots. Optimization of an L-012-based method for grapevine cell suspensions. Chitosan is a potent elicitor of the oxidative burst in grapevine cell suspensions. Chitosan triggers an oxidative burst in rice roots. DMSO interferes with the L-012-based chemiluminescence assay. Abstract: Roots are prominent plant-microbe interaction sites and of great biological relevance for many studies. The root response is of interest when searching for potential systemic resistance inducers. Screening of elicitors often focuses on the oxidative burst, the rapid and transient production of Reactive Oxygen Species (ROS). However, to our knowledge, no high-throughput, sensitive methods have been developed for the quantification of ROS released by roots. Here, we report on the development of an L-012-based chemiluminescence bioassay to quantitatively determine the oxidative burst following elicitation events in roots. Rice and grapevine were used as monocot and dicot models. We demonstrate that chitosan, a recognized elicitor in rice cells, was able to elicit ROS production in rice roots. Chitosan also triggered a strong oxidative burst in grapevine cell suspension cultures, while grapevine roots were not responsive. Although this method is broadly applicable, the L-012 probe requires careful consideration of solvents and plant species. Insufficient extracellular ROS, quenching, and the interference of solvents with the probe can undermine the assay sensitivity.